THE STATE OF FUNCTIONAL CAPACITY AND HEALTH OF STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS - Oleksandr Sabirov; Vasyl Pantik; Andriy Shevchuk (Lesya Ukrainka Volyn National University, 2017)
The relevance of the research lies in the fact that the individualization of students' physical education has occupied a prominent place in scientific studies. The goal of the research is to study the state of the functional capacity and health of students of higher educational institutions. Materials and methods of the research: аnalysis and generalization of literary resources, testing and surveys. Results are as follows: the average group parameters of systolic and diastolic blood pressure level of students are within normal limits. The vital capacity of lungs of young men is within the range of 3,98 - 4,3 liters. Conclusions of the research: the obtained data testify that 2,5 % of students have a low level of physical capacity and health, 5,1 %  - have a below midium level of physical capacity and health. Most of the boys (70,9 %) are referred to the normal level of physical capacity and health, 20 % have an above medium level of physical capacity and health and only 1,5 % have a high level of physical capacity and health.